CORRELATION BETWEEN SOLVENCY OF SERBIAN AGRICULTURAL SECTOR AND INVESTMENTS IN ENVIRONMENTAL RESPONSIBILITIES - Stojić, Milena; Pejović, Biljana; Bižić, Vojkan (Economics of Agriculture, 2024)
Whether investment in environmental protection is conditioned by the solvency of agricultural companies, due to the growing importance of environmental sustainability, is the topic of this paper. The goal of the research is to determine, on a sample of 40 agricultural companies, whether investment in environmental protection is conditioned by solvency in a three-year period. Solvency, which is relatively good in the sampled companies, is not correlated with investment in the environment, in the analyzed time period, based on the quantification of descriptive data from the annual report. The level of disclosure of the environmental dimension of the sustainability of agricultural companies in Serbia is at a very poor level and the ESG reporting concept is necessary. The research indicates non-compliance with the legal obligation of non-financial reporting on environmental protection of agricultural companies, which indicates that educational, legal and regulatory measures must be urgently taken in order to make the reporting as representative as possible.